CAPACITY BUILDING IN AGENCIES FOR EFFICIENT AND EFFECTIVE HEALTH TECHNOLOGY ASSESSMENT. (17th October 2016) - Mueller, Debjani; Gutiérrez-Ibarluzea, Iñaki; Schuller, Tara; Chiumente, Marco; Ahn, Jeonghoon; Pichon-Riviere, Andres; García-Martí, Sebastian; Grainger, David; Cobbs, Elizabeth; Marchetti, Marco
Abstract : Objectives: Health technology assessment (HTA) yields information that can be ideally used to address deficiencies in health systems and to create a wider understanding of the impact of different policy considerations around technology reimbursement and use. The structure of HTA programs varies across different jurisdictions according to decision-maker needs. Moreover, conducting HTA requires specialized skills. Effective decision making should include multiple criteria (medical, economic, technical, ethical, social, legal, and cultural) and requires multi-disciplinary teams of experts working together to produce these assessments. A workshop explored the multi-disciplinary skills and competencies required to build an effective and efficient HTA team, with a focus on low- and middle-income settings. Methods: This proceeding summarizes main points from a workshop on capacity building, drawing on presentations and group discussions among attendees including different points of view. Results and Conclusions: The workshop and thus this study would have benefited from a larger variety of stakeholders. Therefore, the conclusions arising from the workshop are not the opinion of a representative sample of HTA professionals. Nonetheless, organizations and speakers were carefully selected to provide a valuable approach to this theme. Thus, these proceedings highlight some of the gaps and needs in the education and training programs offered worldwide and calls for further investigation.